Reconceptualizing the Islamic Penal System: Jarimah, Uqubat, and Taʿzir within the Framework of Maqāṣid al-Sharīʿah and Contemporary Criminal Justice - Arifin Siahaan; Ardiansyah (ISNU Sumatera Utara, 2026)
The penal system in Islamic law is an integral part of the sharia which aims to maintain social order, uphold justice, and protect human dignity. The concept of jarimah as a criminal act in Islamic law is not only understood as a violation of legal norms, but also as a violation of divine provisions derived from the Qur'an and Sunnah. Criminality in Islam is manifested through uqubat which is classified into hudud, qishash-diyat, and taʿzir, each of which has different characteristics, purposes, and legal basis. This research aims to analyze conceptually and normatively the penal system in Islamic law by focusing on the definition of jarimah, forms of uqubat, and the principles of criminal law that underlie it. The research method used is normative legal research with a conceptual, philosophical, and normative-shari'a approach, through the study of the Qur'an, Sunnah, the opinions of the jurists, and Islamic criminal law literature. The results of the discussion show that the penal system in Islamic law is built on the principles of justice, certainty, and benefit, which is reflected in the strict standard of proof of hudud, the proportional nature of qishash-diyat, and the flexibility of taʿzir in responding to social dynamics. The difference in the views of scholars in interpreting the postulates of criminalization confirms that Islamic criminal law has an adaptive character without losing its normative legitimacy. The conclusion of this study emphasizes that the penal system in Islamic law is a comprehensive legal system and oriented towards substantive justice, crime prevention, and protection of maqāṣid al-syarī'ah.